(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper breaks down the technology behind smart glasses along with the advancement in this emerging field keeping in mind the hardware, software and research work which major companies have put in to develop a real-life model. This paper also comprises an analysis on the experience of users with different glasses. We have also talked about the new benchmarks which this technology has set in sectors such as medicine, gaming, corporate, sports, entertainment and many others.